2006
DOI: 10.1159/000095178
|View full text |Cite
|
Sign up to set email alerts
|

Osmoregulation of Taurine Efflux from Cultured Human Breast Cancer Cells: Comparison with Volume Activated Cl<sup>-</sup> Efflux and Regulation by Extracellular ATP

Abstract: The properties and regulation of volume-activated taurine efflux from MDA-MB-231 and MCF-7 cells have been investigated. Volume-activated taurine release from both cell lines was almost completely inhibited by diidosalicylate. DIDS , was more effective at inhibiting swelling-induced taurine release from MCF-7 than from MDA-MB-231 cells. On the basis of comparing taurine, Cl- and I- efflux time courses, it appears that volume-activated taurine efflux does not utilize volume-sensitive anion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…Volume-sensitive taurine release from MCF-7 cells is not increased by the addition of exogenous ATP (Shennan et al 2006). We now show that swelling-induced glycine efflux is also unaffected by ATP (Fig.…”
Section: The Effect Of Atp On Swelling-induced Amino Acid Releasesupporting
confidence: 58%
See 3 more Smart Citations
“…Volume-sensitive taurine release from MCF-7 cells is not increased by the addition of exogenous ATP (Shennan et al 2006). We now show that swelling-induced glycine efflux is also unaffected by ATP (Fig.…”
Section: The Effect Of Atp On Swelling-induced Amino Acid Releasesupporting
confidence: 58%
“…We have previously shown that volume-activated taurine efflux from MDA-MB-231 cells is markedly enhanced by ATP (Shennan et al 2006). In view of this we tested the effect of ATP on swelling-induced AIB, glycine and D-aspartate efflux from MDA-MB-231 cells.…”
Section: The Effect Of Atp On Swelling-induced Amino Acid Releasementioning
confidence: 99%
See 2 more Smart Citations
“…Taurine uptake via TauT could act to maintain the intracellular levels of taurine which subsequently could be used to help MCF-7 cells regulate their volume. In this connection we have evidence that an increase in the cellular hydration state of MCF-7 cells leads to a rapid increase in taurine release from the intracellular compartment via a pathway which is inhibited by DIDS [23]. Therefore, inhibition of taurine uptake by breast cancer cells could compromise cell volume regulation and thus cell survival given that the cellular hydration state is linked to a number of vital processes.…”
Section: The Effect Of Estrogen On Taurine Uptakementioning
confidence: 94%